Rainwater Management Model Development for Agriculture in the Savu Island Semi-Arid Region - Susilawati C.L. (Civil Engineering Dimension, 2012)
Savu Island is a semiarid region with few rainfalls. The meager annual rainfall of about 1,000-1,500 mm that lasts for three to five months tends to cause draught. To cope with this situation, the Author tries to develop a rainwater management model located in Daieko village. This model constitutes an infrastructure that consists of check dam series which are constructed by simulating a computerized model of decision supporting system called “Rainwater Management for Agriculture Decision Support System (RMA-DSS) model” in the research location of Daieko village. Employing a simulated RMA-DSS model; the locations for check-dam series, and dug-wells can be determined, the size of potential irrigable lands can be determined based on water balance analysis of water samples taken from simulated check dams and inundated lands. Through this model the sufficiency of water supply for agricultural purposes and the land size for cultivation area can be predicted with a high degree of certainty.